Vocational education in the Portuguese public secondary school: Perceptions of its main educational agents - Armando Esteves; Maria Luísa Frazão Branco (Arizona State University, 2018)
Vocational education was officially introduced in Portuguese public secondary schools in 2004, within the framework of the Europeanization of national educational policies. The main goals of this initiative were the increase of skilled labor and the diversification of the dual certification training, posing several challenges to schools. In this context, the main objective of the present study is to verify the perception held by the main educational actors of vocational courses in the public secondary school. To achieve this aim, a descriptive study was done using questionnaire surveys at a public secondary school that has offered vocational courses since its inception in 2004. Among the obtained results, it should be highlighted that according to the teachers and the directors, the vocational courses have been an asset to the consolidation of the goals of the educational project of the school, reinforcing its role in the training of qualified young people to the labor market and enhancing their identity, not to mention the remarkable improvement in student's marks.  In the students' point of view, we must take into account the practical nature of the courses and orientation to the labor market, the quality of training, and the promotion of their educational success.